Prevalence of cholera risk factors between migrant Haitians and Dominicans in the Dominican Republic - Andrea J. Lund; Hunter M. Keys; Stephanie Leventhal; Jennifer W. Foster; Matthew C. Freeman (Pan American Health Organization, 2015)
OBJECTIVE: To determine whether cholera risk factor prevalence in the Dominican Republic can be explained by nationality, independent of other factors, given the vulnerability of many Haitians in the country and the need for targeted prevention. METHODS: A cross-sectional, observational household survey (103 Haitian and 260 Dominican) was completed in 18 communities in July 2012. The survey included modules for demographics, knowledge, socioeconomic status, and access to adequate water, sanitation, and hygiene (WASH) infrastructure. Logistic regression assessed differential access to WASH infrastructure and Poisson regression assessed differences in cholera knowledge, controlling for potential confounders. RESULTS: Dominican and Haitian households differed on demographic characteristics. Haitians had lower educational attainment, socioeconomic status, and less knowledge of cholera than Dominicans (adjusted odds ratio [aOR] = 0.66; 95% confidence interval [95%CI] = 0.55-0.81). Access to improved drinking water was low for both groups, but particularly low among rural Haitians (aOR = 0.21; 95%CI: 0.04-1.01). No differences were found in access to sanitation after adjusting for sociodemographic confounders (aOR = 1.00; 95%CI: 0.57-1.76). CONCLUSIONS: Urban/rural geography and socioeconomic status play a larger role in cholera risk factor prevalence than nationality, indicating that Haitians' perceived vulnerability to cholera is confounded by contextual factors. Understanding the social dynamics that lead to cholera risk can inform control strategies, leading to better targeting and the possibility of eliminating cholera from the island.